Politics, Law & Complexity: The Case of the Academic Policies in the European Union - Andrea Pitasi (RIMCIS, 2016)
The theoretical goal of this paper is the development of the connection between politics and law within the model of the complex system especially in the perspective of Niklas Luhmann, in a viewpoint linked with the economic analysis of law. The aim is to describe the differences that truly make the difference in the setting problem of policy or legal decisions more formalized by the subject with their values instead of in a system. Therefore, the vision of Joseph A. Schumpeter about the politics as a kind of market, a sub-kind market where votes are sold and bought it is very important and strategic as a bridge between the macro-systemic and the economic analysis of law becomes even more positive, artificial and global: the more is the scenario, the weaker is the function of the human subject in the decisional process, this also provides a report of the changes in the very idea of citizen in global scenarios, which is the Hypercitizenship.